Exploring Innovative Thinking of Bergson’s Philosophy and Modern Art via Computer-Aided Design—A Case Study with Three Works as Examples - Chung-Ho Tien; Xia-Na Ma; Zi-Hui Sun (Engineering Proceedings, 2023)
The innovative thinking of artists highlights the influence of Bergson’s philosophy on modern art, and the perception of the relationship of the inner essence of “mind and matter” through observing and experiencing daily life helps artists design works according to the artists’ conception. The innovative thinking of learners is based on the creation of art, namely duration, movement, timeliness, and dynamics. We integrated the emotions of creators as the links of the creation of works with the “aesthetic duration” of the viewer, the “movement” rhythm of visual transformation of different “timeliness” provided by the workspace to evoke the “dynamics” of the viewers’ internal thoughts. In this article, the creative thinking of three works, namely Growth, Fisherman, and Virtuality and Reality, was analyzed for learners to discuss how the creators designed their works to connect and reflect their creative thinking and creation with the help of emotion. The results of this analysis of creative thinking helped students understand the process of artistic creation and have the creative characteristics of Bergerson’s philosophy. The emotional elements of the creator need to be integrated to evoke the deepest feelings and help viewers feel the beauty of works to the maximum.